التعليم فى مدارس بيت المقدس الاسلامية فى العصر الأيوبى - ظاهر، عدنان محمد محمود (: كلية الدراسات العليا، الجامعة الأردنية, 1990)
This study aimed to identify the educational role played by the schools of Beit al-Makdis during the Ayyubite period within the context of their basic role education